2010
DOI: 10.1007/s12603-010-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive intervention programmes on patients affected by Mild Cognitive Impairment: A promising intervention tool for MCI?

Abstract: Though both traditional and computer-based cognitive intervention programmes seem to be effective, the computer-based ones present more advantages: 1) they could individualize the programme tailored to the patient's neuropsychological pattern and needs. 2) they permit the user to make an immediate objective comparison with data collected earlier and thus help in setting up a systematic training plan by providing instant value-free feedback. 3) they offer a possibility of a widescale dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 30 publications
(19 reference statements)
0
50
0
4
Order By: Relevance
“…Although the sample was small, this study, as well as ours, showed that cognitive stimulation therapy can reduce cognitive decline in MCI patients. In a recent literature review [45] , the authors concluded that cognitive stimulation/training programs seem to be promising to improve cognitive abilities, subjective memory complaints and emotional states in MCI patients. They also concluded that computer-based interventions seem to be more beneficial for training MCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample was small, this study, as well as ours, showed that cognitive stimulation therapy can reduce cognitive decline in MCI patients. In a recent literature review [45] , the authors concluded that cognitive stimulation/training programs seem to be promising to improve cognitive abilities, subjective memory complaints and emotional states in MCI patients. They also concluded that computer-based interventions seem to be more beneficial for training MCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…adequate control of hypertension and hypercholesterolemia in middle age will decrease vascular dementia and possibly alzheimer's disease. maintaining an interest in meaningful activities such as playing a musical instrument, chess or dancing also decrease the chance of developing dementia (110). appropriate end-of-life care programs should be established for those with end stage alzheimer's disease (111).…”
Section: Resultsmentioning
confidence: 99%
“…Outros estudos comparam os efeitos da intervenção realizada com o apoio do computador com intervenções feitas usando exercícios baseados em tarefas com lápis e papel, mostrando que os benefícios do treino computadorizado são semelhantes às intervenções tradicionais (Faucounau et al, 2010;Peretz et al, 2011;Stürz et al, 2011). Esta dissertação não abordou estudos de treino computadorizado ou envolvendo minorias étnicas, visto que esta literatura tem crescido nos últimos anos e o enfoque deste estudo foi o treino de memória sem o envolvimento de softwares ou minorias étnicas.…”
Section: Treino De Memória Em Idosos Saudáveis E Com Comprometimentounclassified